Burnout amongst Cardiothoracic Surgery Trainees in the UK: Insights from the GMC National Trainee Survey - Comanici, Maria; Jones, Timothy; Raja, Shahzad G. (British Journal of Healthcare and Medical Research, 2025)
Background: Burnout among medical professionals profoundly impacts both individuals and patient care. This study looks into the escalating burnout rates among cardiothoracic surgery trainees in the UK, using data from the General Medical Council National Trainee Survey conducted in 2023. Methods: Survey responses from 45 cardiothoracic surgery trainees were analysed and compared with those of trainees from various other surgical specialties. The survey assessed emotional exhaustion, frustration, and work-related fatigue. Results: Cardiothoracic surgery trainees exhibited a higher burnout rate of 24.4% compared to the overall average for surgical specialties of 22.7% (P=0.9417). A detailed analysis revealed that 60% of trainees experienced a high or very high degree of emotional exhaustion, and 44% reported burnout due to work. These rates have shown an alarming upward trend over the years, with a 351.85% increase in high burnout levels from 2019 to 2023. Conclusion: The data underscores a worrying trend of increasing burnout among cardiothoracic surgery trainees in the UK, with rates significantly higher than the average for other surgical specialties. Addressing the rising burnout rates among cardiothoracic surgery trainees is crucial to ensuring high-quality patient care, a sustainable workforce, and the overall well-being of medical professionals.